PENGARUH KOORDINASI ANTAR FUNGSIONAL YANG MELIPUTI TANGGUNG JAWAB, KOMPETENSI DAN KERJASAMA TIM TERHADAP KINERJA PEMASARAN UKM DI KOTA BANJARMASIN DAN BANJARBARU - Nova Abriano; Ni Nyoman Suarniki (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, The purpose of this research was to determine the variables of responsibility, competence and teamwork have significant influence simultaneously to the marketing performance of SMEs in the city of Banjarmasin and Banjarbaru well as to determine which of the variables of responsibility, competence and teamwork to have a dominant influence in partial the marketing performance of SMEs in Banjarmasin and Banjarbaru. Results of calculations obtained F count is equal to 42.356 this means is greater than the value of F table at 1,979 on the degree of error of 5%, it can be concluded that the variables of responsibility, competence and teamwork have significant influence simultaneously to variable marketing performance of SMEs in the city of Banjarmasin and Banjarbaru. The amount of the contribution of independent variables (X) on the dependent variable (Y), as shown by the coefficient of determination (R2) that R2 is equal to 0.762 or 76.2% against the magnitude of the marketing performance of SMEs in the city of Banjarmasin and Banjarbaru, while the rest influenced by variables another variable is not included in this study is 23.8%. Variables that have the most dominant influence on the marketing performance of SMEs in the city of Banjarmasin and Banjarbaru is variable responsibility because it has the largest t is equal to 8.201.